Mag-welding of repair structures of main gas pipelines - Maksimov, Sergii; Oleinik, Oleg; Gavrilyuk, Anatoliy (Publishing House of Lviv Polytechnic National University, 2016)
Investigations on the development of a basic technology of the shielded-gas mechanized arc welding of strengthening structural elements which are used in repair of main gas pipelines were carried out. It is shown that the advanced welding wires Sv08G2S, Е71Т-1, DW-50, DW-A55 are in compliance with the requirements for providing the necessary level of mechanical characteristics, impact toughness of weld metal, content of diffusive hydrogen in the deposited metal and can be recommended for application in the further testing of technology for repair of the operating pipelines under the field conditions. The carried out works resulted in the working out of documentation on the technology of mechanized arc welding in shielding gases in repair of main gas pipelines of Ukraine.
Keywords: main gas pipeline; repair; arc welding; welded joint; flux-cored wire; cold cracks; preheating; diffusive hydrogen